Sensitivity of plants to changing atmospheric CO2 concentration: from the geological past to the next century. Issue 4 (25th January 2013) - Franks, Peter J.; Adams, Mark A.; Amthor, Jeffrey S.; Barbour, Margaret M.; Berry, Joseph A.; Ellsworth, David S.; Farquhar, Graham D.; Ghannoum, Oula; Lloyd, Jon; McDowell, Nate; Norby, Richard J.; Tissue, David T.; et al.
Summary: The rate of CO2 assimilation by plants is directly influenced by the concentration of CO2 in the atmosphere, c a . As an environmental variable, c a also has a unique global and historic significance. Although relatively stable and uniform in the short term, global c a has varied substantially on the timescale of thousands to millions of years, and currently is increasing at seemingly an unprecedented rate. This may exert profound impacts on both climate and plant function. Here we utilise extensive datasets and models to develop an integrated, multi‐scale assessment of the impact of changing c a on plant carbon dioxide uptake and water use. We find that, overall, the sensitivity of plants to rising or falling c a is qualitatively similar across all scales considered. It is characterised by an adaptive feedback response that tends to maintain 1 −  c i / c a, the relative gradient for CO2 diffusion into the leaf, relatively constant. This is achieved through predictable adjustments to stomatal anatomy and chloroplast biochemistry. Importantly, the long‐term response to changing c a can be described by simple equations rooted in the formulation of more commonly studied short‐term responses.   Contents     Summary 1077 I. Introduction 1078 II. Atmospheric CO2 concentrations through time 1079 III. Plant sensitivity to CO2 at geological timescales 1080 IV. Plant sensitivity to CO2 over the last 200 yr 1081 V. Increased water‐use efficiency? 1084 VI. Simple formulation of stomatal conductance in land surface models for simulating long‐term CO2 response 1087 VII. Conclusions 1088   Acknowledgements 1089   References 1089